Interpreting the Baroque Prelude from Prelude and Fugue no.2 in C minor BWV 847 by J. S.Bach / Nur Fatira Hamdi Mohd Farid Hamdi - Mohd Farid Hamdi, Nur Fatira Hamdi (2023)
Piano interpretation is an important playing style for interpreting pieces of music. Indeed, it is intended to add to the knowledge of the appropriate method of interpretation for as elected work. This study is an investigation into the framework and characteristics of the interpretation of piano pieces during the Baroque period. To refine the investigation, my research focused on the relevant characteristics of the performed parts that I specifically identified as Dynamic, Pace, and Pronunciation for "Prelude No. C minor, BWV 847". This study also explains a brief comparative history between the Baroque period and the modern period, because it is important to know the history of Baroque music before the music of the Baroque period is forgotten. The purpose of this study was to define characteristics and create a framework for implementing Prelude and Fugue No. 2 in C minor, BWV 847, which I successfully presented, illustrated and explained the methods. and key techniques used to create an interpretation of the prelude. No. 2 in C minor, BWV 847. I supported detailed evidence regarding the question in chapter four (4) I was able to complete my investigation primarily by analysing Prelude and Fugue No. 2 in C minor, BWV 847 by three performers such as Sviatoslav Richter, Glenn Gould and Andras Schiff. There are the greatest symbols in piano covers.